Interprofessional learning in ambulatory care. (12th February 2018) - Saunders, Rosemary; Dugmore, Helen; Seaman, Karla; Singer, Rachel; Lake, Fiona
Summary: Background: Interprofessional practice amongst health care professionals can facilitate effective collaboration and can improve health outcomes for patients. Interprofessional clinical placements have mainly been established within inpatient settings; however, ambulatory care settings can also provide interprofessional education. This study evaluates an interprofessional placement in ambulatory care for medical and nursing students. Methods: Medical and nursing students undertook a 2‐week interprofessional placement in respiratory, diabetes and chronic pain clinics, as well as within the patient's home. An electronic post‐placement survey including 14 fixed‐response and five open‐ended questions was conducted to evaluate the students' experiences. Results: Ninety‐two students undertook the interprofessional placement: 74% were medical students and 26% were nursing students. The overall response rate was 81%. Students strongly supported the model of clinical supervision with the nurse educator and teaching registrar working collaboratively to facilitate the placement. Both medical and nursing students felt that the placement facilitated the development of interprofessional principles, with 78.7% agreeing or strongly agreeing with the statement 'the clinical placement allowed me to reflect on interprofessional learning and practice'. In terms of future practice, 67% of medical students and 81% of nursing students agreed that 'this placement has altered how [they] will practice as a professional in the future'. Interprofessional practice can facilitate effective collaboration and can improve health outcomes for patients Discussion: Medical and nursing students found that the ambulatory care setting facilitated a mix of learning opportunities that complemented learning from the inpatient setting, and the interactions with other health professionals provided a valuable learning experience that contributed to their understanding of interprofessional practice.